Successful exclusion of left main trunk coronary artery aneurysm and concomitant HeartMate 3 implantation in a patient with a history of infective endocarditis: a case report. Issue 3 (16th February 2023) - Kunioka, Shingo; Tadokoro, Naoki; Fujita, Tomoyuki; Fukushima, Satsuki
Abstract: Background: Coronary artery embolism is a rare, life-threatening complication in patients with infectious endocarditis. Percutaneous transluminal coronary angioplasty is a common treatment; however, a coronary artery aneurysm may develop at the angioplasty site. Case summary: A 33-year-old women had been hospitalized in another institution due to cardiopulmonary arrest caused by embolic occlusion in the left main artery and infective endocarditis on mitral valve. Following extracorporeal membrane oxygenation insertion, she underwent percutaneous transluminal coronary angioplasty of the left main coronary artery and mitral valve replacement. She was transferred to our institution for advanced heart failure care. We immediately upgraded extracorporeal membrane oxygenation to an extracorporeal left ventricular assist device. Despite 6-week adequate medication, her left ventricular function was not improved. She was listed for heart transplantation on post-operative Day 40. Her blood culture showed negative results for 6 weeks. We planned to convert the left ventricular assist device from extracorporeal to implantable. However, pre-operative coronary artery angiography showed a large left main trunk coronary artery aneurysm on the stent site and rapid aneurysm enlargement. Surgery was performed on post-operative Day 48; the aneurysm was left unresected; its inflow and outflow arteries were completely ligated and supplemented by coronary artery bypass grafting. HeartMate 3 was implanted concomitantly, and the post-operative course was uneventful. Discussion: Coronary artery aneurysm at the angioplasty site was treated with adequate antibiotic therapy and simply ligation of the proximal and distal flow arteries of the aneurysm. Aneurysm ligation reduced invasive surgical procedures and provided time for concomitant surgery.